'You're not just learning it, you're living it!' Constructing the 'good life' in Australian university online promotional videos. Issue 5 (3rd September 2017) - Gottschall, Kristina; Saltmarsh, Sue
ABSTRACT: Online promotional videos on Australian university websites are a form of institutional branding and marketing that construct university experience in a variety of ways. Here we consider how these multimedia texts represent student lifestyles, identities and aspirations in terms of the 'good life'. We consider how the 'promise of happiness' is deployed to appeal to perceived consumer desires within the local student market, as well as within the highly competitive global knowledge economy. These texts position university students as youthful, attractive, active and fun, and depict student life as being about leisure and pleasure. Such representations promote cultural and social entitlement to the 'good life' as if synonymous with choice, participation and success in higher education. Learning and scholarship are depicted as secondary activities. We also contend that claims to cosmopolitanism and consumerism are framed by racialised entitlements where Whiteness remains both a commodity and norm.